Polymerase-guided base editing enables in vivo mutagenesis and rapid protein engineering - Aaron Cravens (Nature Portfolio, 2021)
Existing in vivo mutagenesis tools are limited by low mutation diversity and mutation rates. Here the authors present TRIDENT for targeted, continual and inducible diversification of genes of interest using deaminases fused to T7 RNA polymerase.